Fulminant myocarditis caused by immune checkpoint inhibitor: a case report and possible treatment inspiration - Zhijie Liu; Yiming Fan; Jun Guo; Ning Bian; Dongdong Chen (ESC Heart Failure)
Abstract Immune checkpoint inhibitors (ICIs) have become a new hope for many patients with advanced cancer by blocking tumour immune evasion. However, with the widespread use of ICIs, immune‐related adverse events (irAEs) have also been discovered and reported increasingly. Immune‐related myocarditis, the most dangerous one of irAEs, still has high mortality in the context of the current treatment. We report the case of a 60‐year‐old female with fulminant myocarditis induced by ICIs, which caused her to experience frequent ventricular arrhythmias such as ventricular fibrillation and heart failure. She was successfully treated with current mainstream therapies for immune‐related myocarditis and additional treatment of sacubitril–valsartan and dapagliflozin. The intriguing observation that the patient condition recovered relatively rapidly in this case shows a possible treatment inspiration, which may be helpful for treating ICIs‐associated myocarditis and improving cancer patients' clinical prognosis.